EphB2 Deficiency Induces Depression-Like Behaviors and Memory Impairment: Involvement of NMDA 2B Receptor Dependent Signaling - Zhen, Linlin; Shao, Tuo; Luria, Victor; Li, Gaowen; Li, Zhi; Xu, Ying; Zhao, Xin (Frontiers in Pharmacology, 2018)
Receptor tyrosine kinase EphB2 mediates development of the neurogenic niche of excitatory neurons, suggesting the possibility that its inactivation plays a role in neuropsychiatric disorders including depression and memory impairment. While N-methyl-D-aspartate (NMDA) receptor is involved in regulating memory formation and neurogenesis in adult animal, it remains unclear how NMDA receptor subtypes mediate depression and cognitive deficits caused by EphB2 loss. The present study shows that EphB2 inactivation results in depression-like behaviors, memory impairment and defects of adult hippocampal neurogenesis. Compared to wild-type littermates, EphB2 KO mice exhibited depression-like behavior and deficits in spatial memory and cognition in forced swimming, tail suspension, Morris water maze, object recognition test and object location test. These behavioral abnormalities were accompanied by substantial decreases in the number of BrdU+ progenitor neurons, phosphorylation of cAMP-response element binding protein (pCREB) and brain derived neurotrophic factor (BDNF), and increased NMDA receptor 2B (NR2B) expression. These molecular, cellular and behavioral alterations induced by EphB2 inactivation were reversed by NR2B antagonist Ro25-6981, suggesting that EphB2 functions to prevent the progression of depression-like behavior and memory impairment by downregulating NR2B. Our findings highlight that NR2B is responsible for EphB2-dependent behavioral and morphological changes. EphB2 may thus be as an important candidate target for treating psychiatric and cognitive disorders.